Lipid and Transcriptional Regulation in a Parkinson's Disease Mouse Model by Intranasal Vesicular and Hexosomal Plasmalogen-Based Nanomedicines - Wu, Yu; Wang, Jieli; Deng, Yuru; Angelov, Borislav; Fujino, Takehiko; Hossain, Md Shamim; Angelova, Angelina (Advanced healthcare materials, 2024)
Plasmalogens (vinyl-ether phospholipids) are an emergent class of lipid drugs against various diseases involving neuro-inflammation, oxidative stress, mitochondrial dysfunction, and altered lipid metabolism. They can activate neurotrophic and neuroprotective signaling pathways but low bioavailabilities limit their efficiency in curing neurodegeneration. Here, liquid crystalline lipid nanoparticles (LNPs) are created for the protection and non-invasive intranasal delivery of purified scallop-derived plasmalogens. The in vivo results with a transgenic mouse Parkinson's disease (PD) model (characterized by motor impairments and α-synuclein deposition) demonstrate the crucial importance of LNP composition, which determines the self-assembled nanostructure type. Vesicle and hexosome nanostructures (characterized by small-angle X-ray scattering) display different efficacy of the nanomedicine-mediated recovery of motor function, lipid balance, and transcriptional regulation (e.g., reduced neuro-inflammation and PD pathogenic gene expression). Intranasal vesicular and hexosomal plasmalogen-based LNP treatment leads to improvement of the behavioral PD symptoms and downregulation of the Il6, Il33, and Tnfa genes. Moreover, RNA-sequencing and lipidomic analyses establish a dramatic effect of hexosomal nanomedicines on PD amelioration, lipid metabolism, and the type and number of responsive transcripts that may be implicated in neuroregeneration.
Keywords: Administration, Intranasal; liposomy; Liposomes; myši transgenní; Nanoparticles; Nanomedicine; Gene Expression Regulation; Disease Models, Animal; in vivo Parkinson's disease transgenic mouse model; Mice; nanomedicine; regulace genové exprese; aplikace intranazální; Parkinsonova nemoc; Lipid Metabolism; modely nemocí na zvířatech; zvířata; hexosomes; Plasmalogens; metabolismus lipidů; nanomedicína; Parkinson Disease; nanočástice; myši; liquid crystalline lipid nanoparticles; Mice, Transgenic; plasmalogeny; RNA‐seq; Animals